Transformation in the Wisdom Books of the Hebrew Bible and its application to the context of Southern Africa - S. Fischer (Acta Theologica)
This article deals with the transformation of theology and society through biblical wisdom. The first section explores the realms of wisdom and the relevance of king Solomon for the wisdom tradition. The second section shows how the books of Job and Proverbs transformed other parts of the Hebrew Bible. The third section explores the transformation of Southern African theology and society through the books of Job and Proverbs. The book of Job is viewed as a paradigm for HIV-positive people. The book of Proverbs is expounded upon with reflections on the ubuntu principle and the postcolonial-critical method Imbokodo. It is shown how folk sayings can be relevant for the transformation of South African university education and how biblical proverbs may transform folk proverbs. Finally, the article proposes that a secular society should be an enabler of different religious traditions.